What Is It Like to Be Schrödinger’s Cat? And Other Tales from the Edge of Planetarization - Löffler, Davor (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Davor Löffler Title (English): What Is It Like to Be Schrödinger’s Cat? And Other Tales from the Edge of Planetarization Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 106-111 Page Count: 6 Citation (English): Davor Löffler, “What Is It Like to Be Schrödinger’s Cat? And Other Tales from the Edge of Planetarization,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 106-111.